Vaccines against Coronavirus Type 19: An Overview - Makwan Abdulkareem (Al-Anbar Medical Journal)
Vaccines are biological agents that provide immunity against certain diseases [1]. Vaccination is an effective technique for prevention of infection and control outbreak of a wide range of infectious diseases (https://apps.who.int/iris/handle/10665/344476). Several types of vaccines are available, including; live-attenuated, inactivated, messenger RNA (mRNA), toxoid, and viral vector, or in the form of subunit, recombinant, polysaccharide, or conjugate vaccines [2]. Weill Hallé and Raymond Turpin used BCG vaccine on human for first time at 1921 [3]. The process of developing a new vaccine is very complex and takes around 11-19 years till marketing approval [4].